Analisis Kualitas Pelayanan Tenaga Administrasi Rumah Sakit terhadap Kepuasan Pasien di Unit Instalasi Rawat Jalan di Rumah Sakit - Shulystiawaty Desy Resky; Muhajrin Muhajrin; Irwan Irwan (Lembaga Pengembangan Kinerja Dosen, 2024)
The quality of health services is a level that shows the perfection of health services that can create a sense of satisfaction in every patient. Service quality has a positive and significant relationship with the level of patient satisfaction that cannot be denied. By showing the high and low level of patient satisfaction is influenced by the high and low quality of service provided. Service quality starts from patient needs and ends at patient expectations. Satisfied patients are a very valuable asset because if patients are satisfied they will continue to use the services of their choice, but if patients are dissatisfied they will tell others twice as great about their bad experiences. So if there is dissatisfaction with the patient, it is something that needs to be considered. This study aims to determine the analysis of the quality of hospital administration services on patient satisfaction in the outpatient installation unit at the Hospital. This study uses an analytical observational design based on crosssectional, quantitative analysis. The population in this study were 10444 patients. The sampling technique used Accidental sampling, with a sample of 100 samples. The instrument in this study was a questionnaire, the data analysis used was simple linear regression. This study shows that all indicators of service quality (Tangible, Reliability, Responsiveness, Assurance, Emphaty) together have a positive influence on the quality of service of hospital administrative personnel on patient satisfaction in the outpatient installation unit at the Hospital.